O18 Internet testing for chlamydia reported through national surveillance in england. (8th June 2017) - Hollis, Emma; Harb, Ana; Talebi, Alireza; Shah, Ammi; Connor, Nicky
Abstract : Introduction: To support and monitor growth of online testing, the National Chlamydia Screening Programme published guidance on commissioning online testing services. Coding was amended in national surveillance systems to differentiate tests requested online from testing in other venues. Methods: National surveillance data from January 2015–September 2016 were linked to the IMD 2015 and ONS urban rural classification indices to analyse the trends in online testing and test positivity by gender for 15–24 year olds. Patterns of repeat testing were explored. Results: 163, 062 tests and 13, 422 diagnoses were reported from online services covering 89% of local authorities in England. Test positivity was higher in men (10% vs. 7.6% women; RR 0.80, p<0.0005 ), residents of urban areas (8.4% vs. 7.4% rural; RR 1.08, p=0.002 ) and those living in the most deprived areas of England (9.6% vs 7.0% least deprived; RR 0.79, p<0.0005 ). Test positivity online was higher than in general practice (8.2% vs GP 6.1% p<0.0005) and lower than in specialised sexual health services (8.2% vs 9.9% GUM and 9.5% SRH p<0.0005). In 2015, 18% of online testers had a subsequent online test within 6 months. Test positivity was higher at first than subsequent test (8.5% vs 7.3%). Discussion: Patterns in online test positivity were comparable with those found in other services suggesting that they are used by the population at risk not just the 'worried well'. Around 1-in-5 of those testing online had subsequent online tests. These findings support the provision of online testing services as well as face-to-face venues.